Comparison of different sampling and treatment methods in order to reconstruct plant economies at the Eneolithic pile-dwellings of Strojanova voda and Maharski prekop at Ljubljansko barje - Tolar, Tjaša (Arheološki vestnik, 2018)
The results of archaeobotanical research at the pile-dwellings of Strojanova voda and Maharski prekop are presented. The Eneolithic sites are located at the south-eastern part of Ljubljansko barje marshes, Slovenia and are dated to around the mid-4th millennium BC. The methodological approaches to archaeobotanical research at the two sites vary considerably. At Strojanova voda, profile sampling was carried out in 2012. Waterlogged archaeobotanical samples were treated and examined with fine wet sieving in the laboratory. At the Maharski prekop, the samples were surface sampled in 2005. Large quantities of sediment samples from the cultural layer were rough washed over sieves on the field; organic fractions caught on the sieves were dried and then examined. In addition to methodological applications, some common conclusions about the nutrition habits of the Eneolithic pile-dwellers can be made on the basis of the results of both studies. In addition to gathering edible wild plants, especially forest fruits and nuts, the inhabitants also grew einkorn, emmer, barley, peas, opium poppy and flax, and possibly also turnip. At Strojanova voda, numerous remains of crushed red dogwood seeds/fruits were found. Red dogwood is a plant with inedible fruits, the purpose of which is still being explored. Plant remains also contribute to the reconstruction of ecological conditions in the immediate vicinity of pile-dwellings.